Detection and Monitoring of Damage Status and Infestation by Spodoptera frugiperda in Maize Crops in Luxor Region, Egypt - Mohamed Sabry Bakry, Moustafa; Thuraya A.A. M. Al-Saadi; M. Aljedani, Dalal; N. F. Abdel-Baky; H.Y. Mohamed, Lamiaa (Universitas Andalas, 2024)
The fall armyworm (Spodoptera frugiperda) is a serious crop pest that destroys maize plants in Egypt and the world, leading to reduced quality and quantity of the maize crop. We conducted this study to monitor and determine the damage status and infestation frequency of S. frugiperda on maize plants in Luxor Governorate, southern Egypt. The sampling date was set with the first observable occurrence of fall armyworm at the study site. Forty randomly selected corn plants (ten plants from each replicate) were evaluated and estimated weekly until harvest. The total number of plants used for sampling was 960 plants during the two seasons. The invasion and damage of maize plants by S. frugiperda started at the age of 16 days after sowing until the time of harvest, i.e. S. frugiperda larvae were detected on maize plants during the period from the third week of June until the maize harvest. In terms of number of larvae, number of plants infested with larvae, percentage of infestation, and percentage of damage intensity, three peaks were recorded in each season, occurring at 30, 58 and 86 days after sowing in 2021 and 2022, respectively. Our study shows that the number of damaged plants was higher than the number of infected plants throughout the season. Thus, the percentage of plants damaged by S. frugiperda increased as the timing of corn plant inspections increased during the two seasons. The results indicate that monitoring plant inspections at key times during the growing season can provide crucial data to help farmers implement timely control measures.